Hydrodynamics of biophase-gas-liquid systems in a vessel equipped with vertical tubular baffles - Major-Godlewska, Marta; Cudak, Magdalena (Chemical and Process Engineering, 2025)
The influence of the impeller type, impeller speed, volumetric gas flow rates, type of sugar and type of yeast on the hydrodynamics (gas hold-up and residence time of gas bubbles) in a vessel with 24 vertical tubular baffles has been presented in this paper. The measurement of hydrodynamics was conducted in the vessel with inner diameter D = 0:288 m and liquid height of H = 0:288 m. Three different agitators were used in the experimental study. Seven different series, three of which refer to the two-phase system and four to the three-phase system were mixed in the vessel. The influence of gas flow number, Weber number, the mass fraction of aqueous sugar solution ci , and mass fraction of yeast suspension yss for twoand three-phase systems on the gas hold-up φ were described mathematically. These equations do not have equivalents in the literature.